An experimentally driven high-throughput approach to design refractory high-entropy alloys. (November 2022) - Lee, Chanho; Xie, Dongyue; Kyle Derby, Benjamin; Kevin Baldwin, Jon; Tandoc, Christopher; EI Atwani, Osman; Hu, Yong-Jie; Valdez, James A.; Li, Nan; Fensin, Saryu J.
Graphical abstract: Highlights: Development of experimentally driven, high-throughput, high-entropy alloy design strategy via physical vapor deposition (PVD) technique. The yield strength and ductility of these 63 Nb-Ti-V-Zr HEAs were quantitatively determined, calculating the two major solid-solution strengthening components (atomic-size and elastic-modulus mismatches) and d -parameters. Down-selection of the compositions, which would potentially exhibit optimized mechanical properties (high strength and good ductility) in Nb-Ti-V-Zr HEA systems via high-throughput alloy manufacturing, theoretical predictions, and experimental approaches. Abstract: High-entropy alloy (HEA) design strategies have been limited to theoretical/computational approaches due to their compositional complexity and extremely large compositional parameter space. In this work, we developed an experimentally driven, high-throughput, HEA design approach using a physical vapor deposition (PVD) technique and coupled it with nanomechanical testing to accelerate material design for structural applications. The PVD technique enabled the formation of a compositional gradient across a thin-film sample. Specifically, a 10 cm wafer was used to manufacture a continuous set of 80 HEA compositions within the Nb-Ti-V-Zr family using a single deposition cycle. By using the solid-solution strengthening theory and estimated parameter properties, the strength and ductility of these HEA compositions were quantitatively determined/predicted and then experimentally verified by nano-indentation hardness test. Consequently, 7 refractory HEA compositions were successfully down-selected, which has a high propensity to have a balanced mechanical property.